Understanding thermomechanical failure of athletic textiles via the pendulum skid method. Issue 10 (May 2019) - Gregory, Shawn Alan; Swarup, Keshav; Lo, Christopher; Dwyer, Ryan; Davidson, Michael; Monroe, Timothy; Spivey, Colten; Realff, Mary Lynn
Fiber textiles worn by some athletes and basketball and volleyball players experience higher than usual thermomechanical stresses compared to everyday garments because these athletes slide and dive on hardwood courts. Common textile testing procedures, such as the Martindale abrasion tester, effectively test textiles under modest loads and thousands of cycles, but this methodology does not suffice for athletic textiles. In addition, there is not a robust model nor a repeatable test that mimics high thermomechanical stress on fabrics and provides insights on fabric abrasion resistance. We present a model to calculate the temperatures and strain rates that are seen by fabrics undergoing thermomechanical deformation. To enable validation of the model, a fabric pendulum abrasion tester, an adaptation of the Cooper pendulum skid tester, was developed. The tester characterizes high-strain fabric abrasion deformation. This adaptation is statistically reliable and induces repeatable and realistic fabric failure within tens to hundreds of cycles, proving to be analogous to the loads athletes place on their textiles. Analog electronics on the pendulum abrasion tester generate real-time temperature and velocity profiles. A series of 11 unique athletic fabrics were abrasion tested, and it was found that fabrics with macroporosity experience the largest abrasion degradation. Significant degradation sites were further explored using scanning electron microscopy and X-ray diffraction analysis, and it was shown that thermomechanical loading's effect on fiber microstructure is a function of the fabric construction. This novel abrasion tester and quantitative relationships between fabric structure and degradation mechanisms will enable more data-driven decisions when designing textiles for thermomechanical loads.